دور قسم ترقية اللغة لترقية مهارة الكلام الطالبات في معهد دار السلام كونتور للبنات الحرم الأول - Joana Septianti Fajarina (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2021)
The goal of this study was to describe the role of central language improvement section of Modern Islamic Boarding School Gontor for Girl to improve student’s speaking skill in their language event. Research method used to collect data is observation, interview and reporting, the approach used is a qualitative method. The result of this study is the central language improvement holding many language events to motivate students in their Arabic speaking and to improve student’s speaking skills.